Cytotoxic T‐lymphocyte‐associated protein 4 in gastric cancer: Prognosis and association with PD‐L1 expression. Issue 7 (13th July 2021) - Pereira, Marina Alessandra; de Castria, Tiago Biachi; Ramos, Marcus Fernando Kodama Pertille; Dias, André Roncon; Cardili, Leonardo; de Moraes, Rafael Dyer Rodrigues; Zilberstein, Bruno; Nahas, Sergio Carlos; Ribeiro, Ulysses; de Mello, Evandro Sobroza
Abstract: Background: Cytotoxic T‐lymphocyte‐associated protein 4 (CTLA‐4) is one of the most studied immune checkpoint in gastric cancer (GC). However, the prognostic role of CTLA‐4 expression in GC is poorly described. This study aimed to evaluate CTLA‐4 expression in GC and its impact on survival, including patients treated with standard platinum‐based chemotherapy (CMT), and association with PD‐L1 expression. Methods: All GC patients who underwent D2‐gastrectomy were investigated retrospectively. Tumor samples were examined for CTLA‐4 and PD‐L1 by immunohistochemistry. Tumor‐infiltrating inflammatory cells, including CD4 + and CD8 + , were also examined. Results: Among the 284 GC patients included, 159 (56%) were CTLA‐4 positive and the remaining 125 (44%) were classified as negative. CTLA‐4 positive GC was associated with increased inflammatory cell infiltration ( p  < 0.001), high CD8 + T cells ( p  = 0.016) and PD‐L1 expression ( p  = 0.026). Considering GC referred for treatment, CTLA‐4 negative patients who received CMT had a significant improvement in disease‐free survival compared to untreated CLTA‐4 negative ( p  = 0.028). In multivariate analysis, GC positive for both CTLA‐4 and PD‐L1 had a prognostic impact on survival. Conclusion: CTLA‐4 positive was associated with PD‐L1 expression and a high tumor‐infiltrating CD8 + T cells. Accordingly, positivity for both CTLA‐4 and PD‐L1 was an independent factor associated to better survival in GC patients.